The two-echelon city logistics system with on-street satellites. (January 2020) - Li, Hongqi; Liu, Yinying; Chen, Kaihang; Lin, Qingfeng
Highlights: The two-echelon city logistics system with on-street satellites (2E-CLS-OS) is introduced. On-street satellites have certain maximal transshipment capacity in different time windows. A mixed integer linear programming model for the 2E-CLS-OS is proposed. The CW algorithm followed by the variable neighborhood search phase is provided. 20 small-scale instances and 33 realistic instances are solved. Abstract: In the two-echelon city logistics system, satellites enable cargo transshipment. Considering on-street satellite phenomena in city logistics practices and the concept of road space sharing between delivery operations and city traffic, we introduce the two-echelon city logistics system with on-street satellites (2E-CLS-OS). The 2E-CLS-OS uses time windows and satellite transshipment constraints to make routes of each of the two echelons interacting. At various time windows of on-street satellites, the real-time transshipment capacity needed by the transshipment operation is constrained by the permitted maximal transshipment capacity and the occupied transshipment capacity. The mathematical formulation for the 2E-CLS-OS is developed. The variable neighborhood search (VNS) heuristic is provided, based on the initial solution constructed by the savings-based heuristic (CW). The model formulation and the VNS are tested by using 20 randomly-generated small-scale instances. The VNS is used to solve 33 realistic instances with up to 30 on-street satellites and 900 customers. The economic difference between the electric vehicles and diesel ones on the second echelon and the impact of varying the truck capacity and the electric tricycle capacity are experimentally analyzed.